Medicinal values of Elaeis guineensis and Raphia hookeri wines - CO, Ibegbulem; CS, Alisi; P, Nwankpa; BA, Amadi; MA, Agiang; VS, Ekam (Journal of Research in Biology, 2012)
The medicinal values of fresh Raphia hookeri and Elaeis guineensis wines were evaluated. Face-to-face interview questionnaire-based ethno-medical survey on 1000 randomly selected families in some southeastern and southsouthern states in Nigeria on the use of the palm wines as antimicrobial agents, vehicles for antimicrobial agents, galactogogues in postpartum mothers and prophylactic agents against malaria in ethno-medicine were carried out. The presence of bioactive phytochemical and biochemical constituents with reported pharmacological activities were detected and their biochemical modes of action were proposed. In conclusion, the antimicrobial values of the wines are phytochemical and ethanol mediated, their lactogenic effects are saponin-mediated increases in serum prolactin content and their prophylactic effect is by the inhibition of the intra-erythrocytic plasmodial growth.